Biomimetic non-classical crystallization drives hierarchical structuring of efficient circularly polarized phosphors - Li-Zhe Feng; Jing-Jing Wang; Tao Ma; Yi-Chen Yin; Kuang-Hui Song; Zi-Du Li; Man-Man Zhou; Shan Jin; Taotao Zhuang; Feng-Jia Fan; Man-Zhou Zhu; Hong-Bin Yao (Nature Communications, 2022)
Chiral emitters with high photoluminescence quantum yield are desirable for use in circularly polarized LEDs. The authors demonstrate the transfer of chirality from nanoscale copper iodide clusters to microscale chiral luminescent polycrystals by non-classical crystallization.